Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To demonstrate that [tex]\(\sqrt{q^2 - p^2} \tan \theta = p\)[/tex] given [tex]\(\sin \theta = \frac{p}{q}\)[/tex], we need to follow a series of trigonometric identity manipulations. Here's the step-by-step solution:
1. Express [tex]\(\tan \theta\)[/tex] in terms of [tex]\(\sin \theta\)[/tex] and [tex]\(\cos \theta\)[/tex]:
Recall that [tex]\(\tan \theta = \frac{\sin \theta}{\cos \theta}\)[/tex].
2. Given: [tex]\(\sin \theta = \frac{p}{q}\)[/tex].
3. Find [tex]\(\cos \theta\)[/tex]:
We use the Pythagorean identity that relates [tex]\(\sin \theta\)[/tex] and [tex]\(\cos \theta\)[/tex]:
[tex]\[ \sin^2 \theta + \cos^2 \theta = 1 \][/tex]
Substituting [tex]\(\sin \theta = \frac{p}{q}\)[/tex]:
[tex]\[ \left(\frac{p}{q}\right)^2 + \cos^2 \theta = 1 \][/tex]
[tex]\[ \frac{p^2}{q^2} + \cos^2 \theta = 1 \][/tex]
Solve for [tex]\(\cos^2 \theta\)[/tex]:
[tex]\[ \cos^2 \theta = 1 - \frac{p^2}{q^2} \][/tex]
[tex]\[ \cos^2 \theta = \frac{q^2 - p^2}{q^2} \][/tex]
Take the square root of both sides:
[tex]\[ \cos \theta = \sqrt{\frac{q^2 - p^2}{q^2}} = \frac{\sqrt{q^2 - p^2}}{q} \][/tex]
4. Substitute [tex]\(\sin \theta\)[/tex] and [tex]\(\cos \theta\)[/tex] into [tex]\(\tan \theta\)[/tex]:
[tex]\[ \tan \theta = \frac{\sin \theta}{\cos \theta} = \frac{\frac{p}{q}}{\frac{\sqrt{q^2 - p^2}}{q}} = \frac{p}{\sqrt{q^2 - p^2}} \][/tex]
5. Multiply [tex]\(\tan \theta\)[/tex] by [tex]\(\sqrt{q^2 - p^2}\)[/tex]:
[tex]\[ \sqrt{q^2 - p^2} \cdot \tan \theta = \sqrt{q^2 - p^2} \cdot \frac{p}{\sqrt{q^2 - p^2}} \][/tex]
The [tex]\(\sqrt{q^2 - p^2}\)[/tex] terms cancel each other out:
[tex]\[ \sqrt{q^2 - p^2} \cdot \frac{p}{\sqrt{q^2 - p^2}} = p \][/tex]
Therefore, we have shown that:
[tex]\[ \sqrt{q^2 - p^2} \tan \theta = p \][/tex]
The expression is indeed proved.
1. Express [tex]\(\tan \theta\)[/tex] in terms of [tex]\(\sin \theta\)[/tex] and [tex]\(\cos \theta\)[/tex]:
Recall that [tex]\(\tan \theta = \frac{\sin \theta}{\cos \theta}\)[/tex].
2. Given: [tex]\(\sin \theta = \frac{p}{q}\)[/tex].
3. Find [tex]\(\cos \theta\)[/tex]:
We use the Pythagorean identity that relates [tex]\(\sin \theta\)[/tex] and [tex]\(\cos \theta\)[/tex]:
[tex]\[ \sin^2 \theta + \cos^2 \theta = 1 \][/tex]
Substituting [tex]\(\sin \theta = \frac{p}{q}\)[/tex]:
[tex]\[ \left(\frac{p}{q}\right)^2 + \cos^2 \theta = 1 \][/tex]
[tex]\[ \frac{p^2}{q^2} + \cos^2 \theta = 1 \][/tex]
Solve for [tex]\(\cos^2 \theta\)[/tex]:
[tex]\[ \cos^2 \theta = 1 - \frac{p^2}{q^2} \][/tex]
[tex]\[ \cos^2 \theta = \frac{q^2 - p^2}{q^2} \][/tex]
Take the square root of both sides:
[tex]\[ \cos \theta = \sqrt{\frac{q^2 - p^2}{q^2}} = \frac{\sqrt{q^2 - p^2}}{q} \][/tex]
4. Substitute [tex]\(\sin \theta\)[/tex] and [tex]\(\cos \theta\)[/tex] into [tex]\(\tan \theta\)[/tex]:
[tex]\[ \tan \theta = \frac{\sin \theta}{\cos \theta} = \frac{\frac{p}{q}}{\frac{\sqrt{q^2 - p^2}}{q}} = \frac{p}{\sqrt{q^2 - p^2}} \][/tex]
5. Multiply [tex]\(\tan \theta\)[/tex] by [tex]\(\sqrt{q^2 - p^2}\)[/tex]:
[tex]\[ \sqrt{q^2 - p^2} \cdot \tan \theta = \sqrt{q^2 - p^2} \cdot \frac{p}{\sqrt{q^2 - p^2}} \][/tex]
The [tex]\(\sqrt{q^2 - p^2}\)[/tex] terms cancel each other out:
[tex]\[ \sqrt{q^2 - p^2} \cdot \frac{p}{\sqrt{q^2 - p^2}} = p \][/tex]
Therefore, we have shown that:
[tex]\[ \sqrt{q^2 - p^2} \tan \theta = p \][/tex]
The expression is indeed proved.
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.